História, ensino e juventudes: um estudo de caso sobre a cultura histórica entre os jovens de Piraí do Sul, PR (2017-2019) - (:unkn) unknown (Universidade Estadual de Ponta Grossa, 2020)
The present master's thesis presents the results of an investigation on the historical youth culture of students at a school in the municipality of Piraí do Sul, in the state of Paraná, between the years 2017 and 2019. The research development structure was composed in two moments, the first carried out from March to November 2018, with the objective of surveying the relationship of young people with the school experience of teaching History. During this phase that assumed a character of survey and understanding about the subjects and the teaching proposal practiced as historical knowledge, we lived with 222 students distributed in six classes of the three grades of High School. The second moment was dedicated to the in-depth study of the mobilization of students in terms of orientation by the dimensions of historical culture. Based on the scenario seen in the first stage, we worked with a sample of 93 questionnaires from the Resident Project: Observatory of relations between young people, history and politics in Latin America, applied in 2019 at the same institution and with part of the students from our surveys. The general objective of the research was centered on the mobilizations presented by a group of young people, belonging to the city of Piraí do Sul, when positioning themselves on themes that affect historical culture. The guiding question of the work was how the elements of expression of history appear drawn in the youth environment, from their study by the dimensions of historical culture. The interest and possibilities of study were established in Didactics of History, following the contributions of historians such as Luis Fernando Cerri, Oldimar Pontes Cardoso and Rafael Saddi Teixeira. The performance of the exploratory study, during classes, was supported by an inspiration in the ethnographic methodology, as presented by professor Marli Eliza André. Understand as a procedure for discovering and filtering information aimed at further deepening, the situations selected and contemplated in the Resident Project questionnaires were quantified within the Likert scale and systematized by the GNU PSPP Software. The approach to the questions followed a perspective of univariate analysis, based on the central trend to which the data pointed out regarding the group of young people. Among the results found are a group of subjects that expresses appreciation and importance in relation to history in their lives, a strong accent on the means of historical exhibitions present in everyday life, but confidence in those who are part of an institutional control. Among the considerations of the investigation, the exploratory study highlights a tension between the understanding attributed to young people in the school of history teaching and the ways in which these subjects are leading the constitution of their youth. As for the dimensions of cultural orientation, we observed in the data obtained, a youth who expressed a predisposition to the breadth of forms with regard to access and sharing of historical culture to signify their practical life, with emphasis on the aesthetic dimension, in which we identified eleven potential pleasant means of contact with representations about the past.
Keywords: Ensino de História; Jovens; Juventudes; Cultura histórica; History teaching; Young; Youths; Historical culture; CNPQ::CIENCIAS HUMANAS::HISTORIA